Role of Bacteriophages in the Implementation of a Sustainable Dairy Chain - Gutiérrez, Diana; Fernández, Lucía; Rodríguez, Ana; García, Pilar (Frontiers in Microbiology, 2019)
The growing human population is currently facing an unprecedented challenge regarding global food sustainability. Thus, it is of paramount to maintain food production and quality while avoiding a negative impact on climate change and the environment at large. Along the food chain, several practices could compromise future food safety and human health. One example is the widespread use of antibiotics and disinfectants in dairy production, which has contributed to the current antibiotic resistance crisis. Moreover, the uncontrolled release of antimicrobials to the environment poses a significant threat to natural ecosystems. For these reasons, research has recently focused on exploiting natural antimicrobials with the goal of achieving a safer and more sustainable dairy production chain. In this context, bacteriophages, viruses that infect bacteria, may become good allies to prevent and treat diseases in cattle, or be used as disinfectants in dairy facilities and as preservatives in dairy products. This review provides an overview of the current research regarding the use of phages as a global approach to reduce economic losses and food waste, while increasing food safety and reducing the environmental impact of food production. Our current understanding of progress, solutions, and future challenges in dairy production, processing, safety, waste processing, and quality assurance is also discussed.